School Family Partnership Based Parental Interventions for Holistic Early Childhood Development - Nurul Hidayanti Qomariah; Endah Sri Lestari; Lina Revilla Malik; Muryani Muryani; Ely Sofiyati; Afrida Afrida (Ceria: Jurnal Program Studi Pendidikan Anak Usia Dini, 2026)
Parental involvement is an important factor in supporting the achievement of eight dimensions of early childhood graduation, including spiritual, moral, cognitive, social-emotional, language, physical, motor, independence, and creativity aspects. However, the implementation of partnerships between schools and families still faces various obstacles, such as limited parental understanding, suboptimal communication, and lack of continuity of stimulation between home and school. This study aims to analyze the form of parental intervention and formulate a model of intervention based on school and family partnerships that support the achievement of eight dimensions of early childhood graduation. The research uses a qualitative approach with a case study design. Data was collected through in-depth interviews, observations, and documentation studies, then analyzed through the stages of data reduction, data presentation, and conclusion drawn. The results showed that partnerships built through parenting programs, intensive communication, scheduled consultations, and comprehensive child development reporting encouraged active parental involvement in learning assistance and stimulation at home. This intervention has been proven to strengthen the achievement of child development in a sustainable manner.